Customer Segmentation in B2B Professional Services Using RFM Analysis and Ethnographic Insights: Evidence from a 15-Year Longitudinal Study - Imam Arie Mulyanto; Jerry Heikal (Publikasi Indonesia, 2026)
The professional services industry, particularly infrastructure and environmental management consulting, faces increasingly complex challenges in managing long-term business-to-business (B2B) customer relationships. This study employed a mixed-methods approach with a sequential explanatory design. In the initial stage, quantitative analysis was conducted using the Recency, Frequency, and Monetary (RFM) method based on historical transaction data from 150 clients over a fifteen-year period at PT Infratama Yakti, a professional consulting firm. Customer data processing and segmentation were performed using SPSS statistical software to identify distinct behavioral segments, resulting in the consolidation of 27 initial segments into six segment groups. In the subsequent stage, an ethnographic approach was applied to interpret relational dynamics and identify pain points associated with each customer segment. The findings indicate that only a small proportion of clients are classified as strategic key clients; however, this segment contributes the highest economic value and relationship stability. Turn-away clients were identified as the primary focus group, as they fall into the latent churn category, characterized by declining relationship recency despite a history of significant value contribution. Accordingly, the required tactical approach involves issue-based communication or engagement centered on specific challenges relevant to the client’s current condition. Through this approach, weakened relationships can be restored before evolving into permanent churn.